Peningkatan Keterampilan Kader dalam Pembuatan Makanan Pendamping ASI (MP-ASI) Berbahan Dasar Lokal - Septikasari, Majestika; Engkartini, Engkartini (Universitas Nusantara PGRI Kediri, 2019)
Selarang Village is a village in the area of ​​Kesugihan II Health Center in Cilacap Regency where in 2016 there were 14 children under five who suffered from malnutrition. One of the factors that influence children's nutritional status is nutritional intake including complementary feeding (CF). The local-based model of CF can be applied as an alternative in solving child nutrition problems. Monitoring in several posyandu in Selarang Village shows that at the time of giving additional food the usual menu is only in the form of green bean porridge. This is because health cadres in Selarang village have never received information or training on how to make cheap local-based CF that able to fullfil the children's nutritional needs. In an effort to deal with this, training activities were carried out to improve cadre skills in the making of locally based CF. The results of this activity include the knowledge and skills of cadres in making local-based CF is increase